Pengetahuan, Kesiapan Ibu dan Anak dalam Keberhasilan Toilet Training - Sri Lestari; Lina Dewi Anggraeni; Fulgensius Surianto (Universitas Faletehan, 2022)
Toilet training is a learning process or exercise carried out by children so that they can urinate and defecate properly. The age of 18-36 months is a toddler period, where toilet training becomes very important. The achievement of this development is done so that the child is accustomed to being independent and also stimulates further development. The purpose of the study was to determine the factors corelated with the success of toilet training in children aged 18-36 months. This study used a descriptive correlative method through a cross sectional approach. This study used a purposive sampling technique and a sample of 163 respondents, with Kendal tau statistical test. The results showed that there was a relationship between mother's knowledge (p value 0.000), mother's readiness (p value 0.000), and child readiness (p value 0.000) with the success of toilet training. The readiness of mothers and children is very important in supporting the success of child toilet training. Parents, especially mothers, need to increase knowledge and provide simulation motivation to children in order to improve toddler toilet training skills.